Estratégias reprodutivas em serpentes da Tribo Tachymenini (Dipsadidae: Xenodontinae) na região subtropical do Brasil - Loebens, Luiza (2019)
Thamnodynastes strigatus and Tomodon dorsatus are snake’s species of the monophyletic tribe Tachymenini widely distributed in the subtropical Brazil. Thamnodynastes strigatus is mostly arboreal with a nocturnal activity pattern and feeds predominately on anurans and occasionally on rodents, fishes, and lizards. Tomodon dorsatus is predominantly terrestrial with a diurnal activity pattern and feeds exclusively on veronicellid slugs. The aim of this study is to compare the reproductive strategies of T. strigatus and T. dorsatus, analyzing the following aspects: (i) morphological variation and sexual dimorphism; (ii) gametogenic cycle, sperm storage, fecundity, sexual maturity, and reproductive investment. Morphological variation and sexual dimorphism were evaluated by linear and geometric morphometrics, allowing to observe that: T. strigatus has larger body and head size than T. dorsatus, as result of divergence in habitat use and prey consumed; T. strigatus and T. dorsatus showed sexual dimorphism in body size, with females being larger than males as a result of selection for fecundity; females of both species have larger heads than males, indicating larger prey consumption than males. The reproductive biology of the species was evaluated through morphological and histological analyzes, generating the following information: T. strigatus and T. dorsatus are viviparous and present biennial seasonal reproductive cycle, with reproductive activity in spring (Oct-Dec), characteristic phylogenetically conserved in Tachymenini snakes; females of T. strigatus and T. dorsatus can store sperm in utero-vaginal junction receptacles during fall and early winter, allowing fertilization of newly-ovulated egg without successive matings; T. dorsatus males perform sperm storage in the ductus deferens during autumn and winter, a synapomorphy of Squamata that enhances male reproductive success; females of both species invest more in growth than males before reaching sexual maturity due to selection for fecundity; T. dorsatus females reach sexual maturity earlier than males, but T. strigatus shows no difference in age at sexual maturity between the sexes; T. dorsatus males have higher longevity compared to females, while T. strigatus does not have a sex-specific longevity pattern.